IMPLEMENTASI AKAD RAHN PADA PRODUK PEMBIAYAAN MULTI GUNA BERKAH: KONSTRIBUSI TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT - Hajar Shaleha, Siti; Idil Ghufron, Moh. (Penerbit Lafadz Jaya, 2025)
This study examines the implementation of the rahn contract in the Multiguna Berkah Financing program at BMT NU Wonosari and its impact on community welfare. The rahn contract, a collateral-based financing scheme grounded in Sharia principles, offers a financial solution for people needing capital access. However, challenges remain, such as limited public understanding and the effectiveness of the contract mechanism in improving customers’ welfare. This research uses a qualitative descriptive approach, collecting data through in-depth interviews, observations, and documentation. Data analysis follows the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity is strengthened by triangulating sources and methods. The results show that the implementation of the rahn contract at BMT NU Wonosari significantly benefits the community by expanding access to flexible and fair Sharia financing. Customers experience improved economic welfare through easier capital access and more stable business management. Nevertheless, low Sharia financial literacy and administrative challenges in managing collateral remain key obstacles. Therefore, it is necessary to optimize rahn contract socialization and adopt more adaptive policies to ensure wider and sustainable benefits of this financing scheme.